Accuracy of outpatient service data for activity-based funding in New South Wales, Australia. Issue 2 (May 2017) - Munyisia, Esther N; Reid, David; Yu, Ping
Background: Despite increasing research on activity-based funding (ABF), there is no empirical evidence on the accuracy of outpatient service data for payment. Objective: This study aimed to identify data entry errors affecting ABF in two drug and alcohol outpatient clinic services in Australia. Methods: An audit was carried out on healthcare workers' (doctors, nurses, psychologists, social workers, counsellors, and aboriginal health education officers) data entry errors in an outpatient electronic documentation system. Results: Of the 6919 data entries in the electronic documentation system, 7.5% (518) had errors, 68.7% of the errors were related to a wrong primary activity, 14.5% were due to a wrong activity category, 14.5% were as a result of a wrong combination of primary activity and modality of care, 1.9% were due to inaccurate information on a client's presence during service delivery and 0.4% were related to a wrong modality of care. Conclusion: Data entry errors may affect the amount of funding received by a healthcare organisation, which in turn may affect the quality of treatment provided to clients due to the possibility of underfunding the organisation. To reduce errors or achieve an error-free environment, there is a need to improve the naming convention of data elements, their descriptions and alignment with the national standard classification of outpatient services. It is also important to support healthcare workers in their data entry by embedding safeguards in the electronic documentation system such as flags for inaccurate data elements.